1995
DOI: 10.1074/jbc.270.18.10658
|View full text |Cite
|
Sign up to set email alerts
|

The RCC1 Protein Interacts with Ran, RanBP1, hsc70, and a 340-kDa Protein in Xenopus Extracts

Abstract: RCC1 is an abundant, highly conserved, chromatin-associated protein whose function is necessary for the preservation of a properly ordered cell cycle. RCC1 is also necessary for numerous nuclear processes, including nuclear transport and RNA metabolism; and it functions enzymatically as a guanine nucleotide exchange factor for a small, ras-related GTPase called Ran. Studies in several organisms suggest that RCC1 may be part of a large complex containing multiple proteins. There is also evidence that RCC1 assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…The specificity of these interactions for the Ran moiety of the fusion protein is indicated by the observation that none of the Rips associated with the GST moiety alone (Figure 1) nor with a series of control GST fusion peptides that were unrelated to RCC1 and Ran (our unpublished results). A subset of the GST-Ran-associated proteins also interacted with a glutathione-S-transferase-RCC1 fusion protein (GST-RCC1; Saitoh and Dasso, 1995). The bands that associated with both fusion proteins had apparent molecular weights of 340, 72, and 30 kDa.…”
Section: Proteins Associated With Ran In Xenopus Egg Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of these interactions for the Ran moiety of the fusion protein is indicated by the observation that none of the Rips associated with the GST moiety alone (Figure 1) nor with a series of control GST fusion peptides that were unrelated to RCC1 and Ran (our unpublished results). A subset of the GST-Ran-associated proteins also interacted with a glutathione-S-transferase-RCC1 fusion protein (GST-RCC1; Saitoh and Dasso, 1995). The bands that associated with both fusion proteins had apparent molecular weights of 340, 72, and 30 kDa.…”
Section: Proteins Associated With Ran In Xenopus Egg Extractsmentioning
confidence: 99%
“…The bands that associated with both fusion proteins had apparent molecular weights of 340, 72, and 30 kDa. The 72 and 30 kDa bands in the GST-RCC1 fractions were previously identified as the heat-shock cognate protein hsc70 and RanBP1 (Saitoh and Dasso, 1995). (A) GST-Ran (200 jig) was bound with GDP, GDPt3S, GTP, GTP-yS, or GMP-PNP, followed by gel filtration to remove excess nucleotide.…”
Section: Proteins Associated With Ran In Xenopus Egg Extractsmentioning
confidence: 99%
“…As shown in Fig. 11, E and F, losartan, but An amino acid sequence analysis revealed that GLP protein contains a motif similar to that of the RCC1 gene, which is a GEF for small G-protein Ran (52)(53)(54)(55)(56)(57). In addition to a seventandem-repeat motif, GLP has an extra carboxyl-terminal tail that the RCC1 gene does not possess (See Fig.…”
Section: Hypertrophic Effects Of the Glp Gene In Irptcs-irptcsmentioning
confidence: 99%
“…Subsequent studies have shown that the loss of RCC1 function at different points in the cell cycle gives rise to different phenotypes. When cells are shifted to the restrictive temperature in the S-phase, the RCC1 mutation results in an interruption of DNA replication, PCC, and a premature mitosis (Nishimoto et al, 1978; ing protein, ran or TC4 in mammalian cells, spil in S. pombe, and GSP1 and GSP2 in S. cerevisiae (Bischoff and Ponstingl, 1991;Matsumoto and Beach, 1991;Coutavas et al, 1993;Saitoh and Dasso, 1995;Azuma et al, 1996). Both proteins are required for normal cell cycle regulation (Matsumoto and Beach, 1991;Sazer and Nurse, 1994).…”
Section: Introductionmentioning
confidence: 99%